2022
DOI: 10.1101/2022.04.25.489455
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Huntington’s Disease Produces Multiplexed Transcriptional Vulnerabilities of Striatal D1-D2 and Striosome-Matrix Neurons

Abstract: Striatal cell-type-specific vulnerability in Huntington’s disease (HD) preferentially affects dopamine D2R-expressing projection neurons (SPNs), compatible with manifest motor symptomatology in HD. Transcriptional studies of striatal striosome-matrix compartmentalization in HD are, however, limited, despite pathologic evidence for striosome vulnerability aligning with early mood symptomatology. We used single-nucleus RNA-sequencing on striatal samples from two murine models, and rare Grade 1 HD patient tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Numerous disorders that were hypothesized to have a compartment-specific element to their pathology and progression may be more completely understood when studied in a compartment-specific approach, rather than at the wholestriatum level (Crittenden and Graybiel, 2011). For example, early in the clinical course of Huntington disease (HD) MSNs in the striosome degenerate more than those in matrix (Hedreen and Folstein, 1995;Matsushima, 2022). Striosome-dominated degeneration also holds true in later stages of HD for individuals whose symptoms were moodpredominant (Tippett et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous disorders that were hypothesized to have a compartment-specific element to their pathology and progression may be more completely understood when studied in a compartment-specific approach, rather than at the wholestriatum level (Crittenden and Graybiel, 2011). For example, early in the clinical course of Huntington disease (HD) MSNs in the striosome degenerate more than those in matrix (Hedreen and Folstein, 1995;Matsushima, 2022). Striosome-dominated degeneration also holds true in later stages of HD for individuals whose symptoms were moodpredominant (Tippett et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent report found that Lypd1, a peptide marker of VENs, 77 is also selectively enriched in the striosome. 78 If future studies demonstrate that VENs selectively project to the striosome, this association may serve as a substrate for limbic symptoms in compartment-selective neurodegenerative diseases. 16,81 4.5: Relating biases in structural connectivity to functional specialization…”
Section: 3: Network Implications Of Segregated Insulo-striate Connect...mentioning
confidence: 99%